Holocene Artemisia-Chenopodiaceae-dominated grassland in North China: Real or imaginary?. (May 2018) - Li, Nannan; Sack, Dorothy; Gao, Guizai; Liu, Lidan; Li, Dehui; Yang, Xiuyun; Jie, Dongmei; Liu, Hongyan; Shi, Jichen; Leng, Chengcheng
The Songnen grasslands were traditionally thought to be dominated by Artemisia and Chenopodiaceae plants as early as the late Pleistocene. However, increasing evidence has called that interpretation into question. To shed new light on the paleovegetation evolution of the arid and semi-arid steppe in North China, phytolith assemblages preserved in the region's sand-paleosol sequence (section Daike) are used as a proxy for paleovegetation structure. Results show that both the sand and paleosol layers in the Songnen grassland sections contain well-preserved phytoliths attributed to different families of grass. This is the first direct evidence of the nature of the vegetation that existed during the sandy layer episodes. Moreover, the phytolith evidence represented in the samples indicates that plant successions happened within the subfamilies of Poaceae through the time. Referring to phytoliths in modern plants and topsoils, and using statistical analyses, we propose that phytolith assemblages in the section Daike originated from Poaceae-dominant communities rather than an Artemisia -Chenopodiaceae ecosystem. The phytoliths, and evidence from the historical and modern pollen-vegetation relationships, lead to rejection of the hypothesis of a past widespread Artemisia -Chenopodiaceae ecosystem in the Songnen grasslands. Using published radiocarbon and thermoluminescence data, it is proposed that the present Poaceae-dominated grasslands developed as early as the early Holocene. This study also highlights the usefulness of phytolith analysis in paleovegetation reconstruction in arid and semi-arid lands.